2004
DOI: 10.1038/sj.ijo.0802603
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of body size and colon cancer mortality in Japan: The JACC Study

Abstract: OBJECTIVE:To determine whether body size measurements are risk factors for colon cancer death among the Japanese. DESIGN AND SUBJECTS: A nationwide prospective study, the Japan Collaborative Cohort (JACC) Study from 1988 to 1999. The present analysis included 43 171 men and 58 775 women aged 40-79 y who respond to a questionnaire on current weight and height, weight around 20 y of age, and other lifestyle factors. Body mass index (BMI) at baseline and 20 y of age (B-BMI and 20-BMI, respectively) were calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
2
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 31 publications
(65 reference statements)
2
39
2
1
Order By: Relevance
“…Previous studies in men suggest a direct obesity/overweight-colon cancer association, 3,4 as apparent herein, although this is not a universal result. 38 We also found a positive non-significant gradient for rectal cancer, an association that has previously been suggested to be null. 39,40 Three other studies 26,41,42 have reported an excess occurrence of malignant neoplasm of the liver in overweight persons.…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies in men suggest a direct obesity/overweight-colon cancer association, 3,4 as apparent herein, although this is not a universal result. 38 We also found a positive non-significant gradient for rectal cancer, an association that has previously been suggested to be null. 39,40 Three other studies 26,41,42 have reported an excess occurrence of malignant neoplasm of the liver in overweight persons.…”
Section: Discussionsupporting
confidence: 58%
“…The Harvard Alumni Health Study reported a 2.5-fold increase in colon cancer risk for men who were overweight both at college entry and at follow-up (1962 or 1966) compared with their lightest peers (26). In contrast to our findings on weight gain, the Japan Collaborative Cohort Study (23) reported obesity and high weight gain since age 20 years to be associated with increased risk of colon cancer mortality for Japanese women but not men. A population-based case-control study (24) investigated changes in BMI at different times in adulthood and reported a positive association between change in BMI (>10 kg/m 2 ) between both the 20s and the 30s decade and the study recruitment period and colon cancer risk for women, but not men.…”
Section: Discussioncontrasting
confidence: 55%
“…One study reported that this relationship was stronger for older men (6). Others have reported that women but not men with excessive adult weight gain have an increased risk of colon cancer (23,24). Weight gain since age 18 was positively associated with risk of colon adenomas in a case-control study (25).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the links between insulin resistance, obesity, and CRC have been noted, and therefore the important roles of insulin pathway in the etiology of CRC have been clarified (Yam et al, 1996;Tamakoshi et al, 2004). The potential associations between variants of genes encoding components of the insulin pathway and risk of CRC have been investigated in limited studies.…”
Section: Discussionmentioning
confidence: 99%